Malta : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper examines the vulnerability of firms in Malta and investigates the effect of their balance sheets on investment in innovation. The results indicate that, while the financial health of medium and large firms has improved in recent years, vulnerabilities remain in the construction sector and for small and medium enterprises. Firms with weaker balance sheets tend to invest less in innovation, even during good times. Policy implications call for (1) accelerating the restructuring of corporate balance sheets of highly leveraged but viable firms, (2) improving the insolvency framework to allow a fast exit of nonviable companies, and (3) expanding corporate funding options for small and medium enterprises, including via nonbank financing alternatives.